Differences in the Concentration of the Fecal Neurotransmitters GABA and Glutamate Are Associated with Microbial Composition among Healthy Human Subjects - Altaib, Hend; Nakamura, Kohei; Abe, Mayuko; Badr, Yassien; Yanase, Emiko; Nomura, Izumi; Suzuki, Tohru (Microorganisms (Basel), 2021)
Recent studies have shown that the gut microbiota modulates the physical and psychological functions of the host through several modes of action. One of them is mediating the production of active neurotransmitters, such as serotonin and gamma-aminobutyric acid (GABA). GABA is the major inhibitory neurotransmitter in the central nervous system. Here, we analyzed the relationship between fecal GABA concentration and microbial composition in more than 70 human participants. The gut microbiome composition was analyzed using next-generation sequencing based on 16S ribosomal RNA. High-performance liquid chromatography was used to evaluate the neurotransmitters GABA and glutamate. The GABA level was detected in a broad range (0–330 µg/g feces). The participants’ samples were classified into high (>100 µg/g), medium (10–100 µg/g), and low (<10 µg/g) groups, based on fecal GABA concentration. The results reveal that the microbiome of the high-GABA samples had lower alpha diversity than the other samples. Beta diversity analysis showed significant (p < 0.05) separation between the high-GABA samples and others. Furthermore, we surveyed the abundance of specific GABA producer biomarkers among the microbiomes of tested samples. The family Bifidobacteriaceae exhibited high abundance in the microbiome of the high-GABA group. This study demonstrated that Bifidobacterium abundance was associated with high fecal GABA content in healthy human subjects. These results may aid the development of potential probiotics to improve microbial GABA production, which can support the maintenance of the physical and psychiatric health of the host.